Corrosion behavior of N80 tubing steel in the produced water - Arslan Vatansever, Duygu; Arkan Ozdemir, Simge; Cansever, Nurhan; Ilhan Sungur, Esra (YILDIZ TECHNICAL UNIV, 2024)
One of the most common problems encountered in the oil industry is the microbiologically induced corrosion (MIC) of steel equipment by the produced water (PW). In this aspect, PW sample, which is known to contain microorganisms, was taken from Adiyaman oil field and used in corrosion tests of N80 tubing steel. Two different laboratory scale systems, test (with non-sterile PW) and control (with sterile PW), were set up and operated at 70 degrees C over 720 h. For corrosion analysis, the coupons were removed from the laboratory-scale systems at certain time intervals and, gravimetric and electrochemical analyses were carried out. The surface of the coupons was examined by scanning electron microscopy (SEM). The corrosion rates of the test coupons obtained from gravimetric analyses were higher than the control ones during the experiment, and the test coupons were 1.46 times more corroded at the end of the experiment. Additionally, it was determined that the current values of the test coupons were significantly higher than those in the control system (p<0.05). The results of corrosion analyses pointed out that N80 steel was corroded microbiologically. SEM analysis showed that microorganisms were present among the corrosion products. The corrosion data obtained from the control system also indicated that the PW was aggressive for N80 steel.
Keywords: Produced Water; N80 Steel; Microbiologically Induced Corrosion (MIC); Electrochemical Tests, Weight Loss; MICROBIOLOGICALLY INFLUENCED CORROSION; SULFATE-REDUCING BACTERIA; CO2 CORROSION; OIL; CARBON; MICROSTRUCTURE; INHIBITION; IRON; Engineering